Preparation, Physicochemical Characterization, and Microrobotics Applications of Polyvinyl Chloride- (PVC-) Based PANI/PEDOT: PSS/ZrP Composite Cation-Exchange Membrane - Mohd Imran Ahamed; Inamuddin; Abdullah M. Asiri; Mohammad Luqman; Lutfullah (Advances in Materials Science and Engineering)
Poly(3,4-ethylene dioxythiophene): polystyrene sulfonate (PEDOT: PSS) zirconium(IV) phosphate (ZrP) based ionomeric membrane was prepared by a solution-casting method. Subsequently, aniline polymerization was carried out on the surface of the membrane by oxidative chemical polymerization. It was characterized by thermogravimetric analysis/differential thermal analysis/differential thermogravimetry (TGA/DTA/DTG), scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray (EDX) analysis, and Fourier-transform infrared (FTIR) spectroscopy. The membrane was also characterized by ion-exchange properties. The tip displacement investigation of the ionomeric membrane was also carried out. The outcomes demonstrated that the manufactured ionomeric membrane could produce generative strengths (tip powers), and consequently create good displacement. In this manner, the proposed ionomeric membrane was found proper for bending movement actuator that will give a successful and promising stage for smaller-scale mechanical applications.